Genetics of Postlingual Sensorineural Hearing Loss. (3rd April 2020) - Ahmadmehrabi, Shadi; Brant, Jason; Epstein, Douglas J.; Ruckenstein, Michael J.; Rader, Daniel J
Abstract : Literature and clinical practice around adult‐onset hearing loss (HL) has traditionally focused on environmental risk factors, including noise exposure, ototoxic drug exposure, and cardiovascular disease. The most common diagnosis in adult‐onset HL is presbycusis. However, the age of onset of presbycusis varies, and patients often describe family history of HL as well as individual variation in progression and severity. In recent years, there has been accumulating evidence of gene–environment interactions underlying adult cases of HL. Susceptibility loci for age‐related HL have been identified, and genes related to postlingual nonsyndromic HL continue to be discovered through individual reports and genome‐wide association studies. This review will outline main concepts in genetics as related to HL, identify implicated genes, and discuss clinical implications. Laryngoscope, 131:401–409, 2021